A bifunctional enzyme, with separate xylanase and beta(1,3-1,4)-glucanase domains, encoded by the xynD gene of Ruminococcus flavefaciens. - Flint, H J (1993)
Adjacent regions of a Ruminococcus flavefaciens 17 DNA fragment were found to encode xylanase and beta(1,3-1,4)-glucanase activities. Sequencing of this fragment showed that both activities are encoded by a single 2,406-bp open reading frame corresponding to the xynD gene. The predicted product has a characteristic signal sequence that is followed by an amino-terminal domain related to family G xylanases, while the carboxyterminal domain is related to beta(1,3-1,4)-glucanases from several other bacterial species. These two domains are connected by a region of unknown function that consists of 309 amino acids and includes a 30-amino-acid threonine-rich sequence. A polypeptide having a molecular weight of approximately 90,000 and exhibiting xylanase and beta(1,3-1,4)-glucanase activities was detected in Escherichia coli cells carrying the cloned xynD gene. This is one of the first cases in which a microbial polysaccharidase has been shown to carry separate catalytic domains active against different plant cell wall polysaccharides within the same polypeptide. xynD is one of a family of related genes in R. flavefaciens that encode enzymes having multiple catalytic domains, and the amino terminus of XYLD exhibits a high degree of similarity with the corresponding regions of another xylanase, XYLA, which carries two different xylanase catalytic domains.